2007
DOI: 10.1016/j.ejphar.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antinociception by the cannabinoid receptor agonist anandamide and the PPAR-α receptor agonist GW7647

Abstract: The analgesic properties of cannabinoid receptor agonists are well characterized. However, numerous side effects limit the therapeutic potential of these agents. Here we report a synergistic antinociceptive interaction between the endogenous cannabinoid receptor agonist anandamide and the synthetic peroxisome proliferator-activated receptor-α (PPAR-α) agonist 2-(4-(2-(1-Cyclohexanebutyl)-3-cyclohexylureido)ethyl)phenylthio)-2-methylpropionic acid (GW7647) in a model of acute chemical-induced pain. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 17 publications
1
49
0
Order By: Relevance
“…The actions of PEA also may be due the actions of its metabolites, particularly in the repeated dosing study, or downstream targets of this FAA. Recently, activation of the large conductance potassium channel (K CA 1.1, BK, slo) a downstream target of PPAR-α receptor agonists, which may be an important target for PEA, was found to reduce pain in the formalin model and to act synergistically with anandamide to reduce pain (Russo et al, 2007). The PPAR-α receptor agonist GW7647 and anandamide were found to produce synergistic antinociception in this same study.…”
Section: Discussionmentioning
confidence: 49%
“…The actions of PEA also may be due the actions of its metabolites, particularly in the repeated dosing study, or downstream targets of this FAA. Recently, activation of the large conductance potassium channel (K CA 1.1, BK, slo) a downstream target of PPAR-α receptor agonists, which may be an important target for PEA, was found to reduce pain in the formalin model and to act synergistically with anandamide to reduce pain (Russo et al, 2007). The PPAR-α receptor agonist GW7647 and anandamide were found to produce synergistic antinociception in this same study.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, it has been demonstrated that cannabinoid receptor agonists present effect via activation of the PPAR-␥ receptor. Although we did not investigate the participation of endogenous cannabinoids in the antinociceptive action of 15d-PGJ 2 , there is evidence that PPAR-␣ synergizes with cannabinoids to produce analgesia (Russo et al, 2007). Therefore, further studies are necessary to elucidate the contribution of endocannabinoids to the antinociceptive effect of 15d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, even though systemic administration of a selective CB 1 receptor agonist has been shown to increase nicotine selfadministration in rats (Gamaleddin et al, 2012), indirectly enhancing endocannabinoid signaling by FAAH inhibition dampens nicotine-induced firing of dopamine cells in the nucleus accumbens through both PPAR-α and CB 1 receptors (Luchicchi et al, 2010;Melis et al, 2010). Moreover, it has been shown that potentiation of FAE signaling at PPAR-α by FAAH inhibition can have various consequences, including functional interactions with signaling at CB 1 receptors (Russo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%